(x + iy) (2 – 3i) = 4 + i

Given:

(x + iy) (2 – 3i) = 4 + i

Let us simplify the expression we get,

x(2 – 3i) + iy(2 – 3i) = 4 + i

2x – 3xi + 2yi – 3yi^{2 }= 4 + i

2x + (-3x+2y)i – 3y (-1) = 4 + i [since, i^{2 }= -1]

2x + (-3x+2y)i + 3y = 4 + i [since, i^{2 }= -1]

(2x+3y) + i(-3x+2y) = 4 + i

Equating Real and Imaginary parts on both sides, we get

2x+3y = 4… (i)

And -3x+2y = 1… (ii)

Multiply (i) by 3 and (ii) by 2 and add

On solving we get,

6x – 6x – 9y + 4y = 12 + 2

13y = 14

y = \(\dfrac{ 14}{13}\)

Substitute the value of y in (i) we get,

2x+3y = 4

2x + 3(\( \dfrac{ 14}{13}\)) = 4

2x = 4 – (\( \dfrac{ 42}{13}\))

= \(\dfrac{ (52-42)}{13}\)

2x = \( \dfrac{10}{13}\)

x = \( \dfrac{5}{13}\)

x = \( \dfrac{5}{13}\), y =\( \dfrac{14}{13}\)

The real values of x and y are \( \dfrac{5}{13}, \dfrac{14}{13}\)

Answered by Aaryan | 1 year agoShow that 1 + i^{10} + i^{20} + i^{30} is a real number?

Solve the quadratic equations by factorization method only 6x^{2} – 17ix – 12 = 0

Solve the quadratic equations by factorization method only x^{2} + (1 – 2i)x – 2i = 0

Solve the quadratic equations by factorization method only x^{2} + 10ix – 21 = 0

Solve the quadratic equations by factorization method only 17x^{2} – 8x + 1 = 0